Severe Distal Motor Involvement in a Non-compliant Adult With Biotinidase Deficiency: The Necessity of Life-Long Biotin Therapy - Van Winckel, Géraldine; Ballhausen, Diana; Wolf, Barry; Procter, Melinda; Mao, Rong; Burda, Patricie; Strambo, Davide; Kuntzer, Thierry; Tran, Christel (Frontiers in Neurology, 2020)
Biotinidase deficiency is an autosomal recessive disorder in which affected individuals are unable to recycle biotin. Untreated, children usually exhibit hypotonia, seizures, ataxia, developmental delay and/or hearing loss. Individuals diagnosed by newborn screening have an excellent prognosis with life-long biotin supplementation. We report a young adult diagnosed with profound biotinidase deficiency by newborn screening who was asymptomatic while on therapy. At 18 years of age, six months after voluntarily discontinuation of biotin, he developed a progressive distal muscle weakness. Molecular analysis of the BTD gene showed a pathogenic homozygous duplication c.1372_1373dupT (Li, 2014, c.1372_1373insT) p.(Cys458LeufsTer26). Despite 16 months since reintroduction of biotin, muscle strength only partially recovered. Transition to adulthood in chronic metabolic diseases is known to be associated with an increased risk for non-compliance. Neurological findings in this adult are similar to those described in others with adult-onset biotinidase deficiency. Long-term prognosis in non-compliant symptomatic adult with biotinidase deficiency likely depends on the delay and/or severity of intervening symptoms until reintroduction of biotin.